2012
DOI: 10.2131/jts.37.911
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of acetaminophen-induced chronic hepatotoxicity in restricted fed rats: a nonclinical approach to acetaminophen-induced chronic hepatotoxicity in susceptible patients

Abstract: Drug-induced Liver Injury (DILI) is becoming a significant public health issue because of its potential impact, not only on patients but also on the development of new drugs. DILI events are also the main cause of regulatory action pertaining to drugs, including denial of marketing approval, restrictions with respect to clinical indications and withdrawal from the marketplace (Lee, 2003;Smith and Schmid, 2006). Acetaminophen (APAP) is a commonly used and effective analgesic and antipyretic agent for relief of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 64 publications
2
20
0
1
Order By: Relevance
“…Although this did not achieve statistical significance, it does suggest that the paracetamol diet may have caused some low-level damage in some mice which is not measurable in the circulation, at least not after 6 weeks of treatment. Previous animal studies that have dosed once daily, via intraperitoneal injection or oral gavage, for 30-99 days with 75-300 mg/ kg showed no evidence of toxicity as assessed by liver function tests [7][8][9]. Our study, which modelled a more clinically relevant exposure to paracetamol at regular intervals over a full day, as it was consumed in the diet, rather than once daily, appears to confirm these findings.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Although this did not achieve statistical significance, it does suggest that the paracetamol diet may have caused some low-level damage in some mice which is not measurable in the circulation, at least not after 6 weeks of treatment. Previous animal studies that have dosed once daily, via intraperitoneal injection or oral gavage, for 30-99 days with 75-300 mg/ kg showed no evidence of toxicity as assessed by liver function tests [7][8][9]. Our study, which modelled a more clinically relevant exposure to paracetamol at regular intervals over a full day, as it was consumed in the diet, rather than once daily, appears to confirm these findings.…”
Section: Discussionsupporting
confidence: 82%
“…There have been few animal studies of chronic paracetamol exposure. Two rat studies, and one mouse study, showed that low-dose paracetamol administered daily did not cause liver toxicity in the absence of other risk factors [7][8][9]. Several rat and BALB/c mouse studies have found that pretreatment with nontoxic doses of paracetamol for 4-8 days before exposure to a high dose of paracetamol can protect against hepatotoxicity, through mechanisms including reduction in cytochrome (CYP)2E1 activity, and increased glutathione (GSH) levels [10][11][12].…”
mentioning
confidence: 99%
“…Chronic exposure to alcohol decreases autophagic flux by inhibiting the fusion of autophagosomes with lysosomes [87]. This may explain why chronic consumption to alcohol favors APAP hepatotoxicity [88, 89]. Besides induction of autophagy, APAP also induces the formation of mitochondrial spheroids in vivo [90], which are ring-like spherical structures with lumen surrounded by mitochondrial membranes that can contain cytoplasmic material.…”
Section: Autophagy In Acute Liver Injurymentioning
confidence: 99%
“…It is reasonable to anticipate population specific toxicity because the activity of CYP2E1—the major enzyme producing NAPQI—is not yet quantified, while data on the NAPQI detoxification capacity through glutathione conjugation in neonates are also lacking 27 28. Furthermore, immaturity of hepatic transporters or individual patient characteristics like malnutrition may further contribute to specific vulnerability 29 30…”
Section: What Is Not Yet Known About Paracetamol and Pda Closurementioning
confidence: 99%